Akonni TruTip(®) and Qiagen(®) methods for extraction of fetal circulating DNA--evaluation by real-time and digital PCR. - Rebecca C Holmberg (Public Library of Science (PLoS), 2013)
Due to the low percentage of fetal DNA present in maternal plasma (< 10%) during early gestation, efficient extraction processes are required for successful downstream detection applications in non-invasive prenatal diagnostic testing. In this study, two extraction methods using similar chemistries but different workflows were compared for isolation efficiency and percent fetal DNA recovery. The Akonni Biosystems TruTip technology uses a binding matrix embedded in a pipette tip; the Circulating Nucleic Acids Kit from Qiagen employs a spin column approach. The TruTip method adds an extra step to decrease the recovery of DNA fragments larger than 600 bp from the sample to yield an overall higher percentage of smaller molecular weight DNA, effectively enriching for fetal DNA. In this evaluation, three separate extraction comparison studies were performed--a dilution series of fragmented DNA in plasma, a set of clinical maternal samples, and a blood collection tube time point study of maternal samples. Both extraction methods were found to efficiently extract small fragment DNA from large volumes of plasma. In the amended samples, the TruTip extraction method was ~15% less efficient with overall DNA recovery, but yielded an 87% increase in % fetal DNA relative to the Qiagen method. The average percent increase of fetal DNA of TruTip extracted samples compared to the Qiagen method was 55% for all sets of blinded clinical samples. A study comparing extraction efficiencies from whole blood samples incubated up to 48 hours prior to processing into plasma resulted in more consistent % fetal DNA recoveries using TruTip. The extracted products were tested on two detection platforms, quantitative real-time PCR and droplet digital PCR, and yielded similar results for both extraction methods.